2020
DOI: 10.15240/tul/001/2020-4-005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-economic and Demographic Determinants on Self-perceived Health

Abstract: This article presents an overview of the self-reported health status of the population of the European Union Member States (EU-28) in the year 2018 based on Eurostat data. The self-reported health status of the inhabitants of the Slovak Republic has been analyzed in more detail with regard to the availability of individual data of the survey results from the European Statistics of Income and Living Condition (EU-SILC). The aim of the article is to analyse the relationship between social and demographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is not new, that the cohort generation consists of individuals who share the major events in history, which impact personality behaviour including consumer behaviour ( Zwanka and Buff, 2021 ). Current comparison by Jindrová and Labudová (2020) , using European Statistics of Income and Living Condition, showed that some of socio-economic determinants between old and new members of the EU-28 were not very large in 2018, but variable Age had the most substantial influence on self-perceived health. This fact supports the generational approach and claim by Parment (2013) that studying purchasing behaviour of generational cohorts could be very beneficial.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is not new, that the cohort generation consists of individuals who share the major events in history, which impact personality behaviour including consumer behaviour ( Zwanka and Buff, 2021 ). Current comparison by Jindrová and Labudová (2020) , using European Statistics of Income and Living Condition, showed that some of socio-economic determinants between old and new members of the EU-28 were not very large in 2018, but variable Age had the most substantial influence on self-perceived health. This fact supports the generational approach and claim by Parment (2013) that studying purchasing behaviour of generational cohorts could be very beneficial.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The anonymous survey was conducted for 40 consecutive days between April and May 2020 and covered the entire territory of Slovenia; participation in the survey was voluntary and without reward. The data contain self-reported evaluations (perceptions); self-reported perception has been shown to be a useful indicator of health on the individual level -see Karasek (1979) and Jindrová and Labudová (2020).…”
Section: Research Instrument Development and Data Collectionmentioning
confidence: 99%
“…Using this new framing, perceived health has become an outcome of the macro-social context, defined as the social, economic and cultural structures and cycles in which people function. The micro-individual level was also reframed, paying greater attention to social variables that explain perceived health such as education (Ross & Mirowsky, 1999), work status, income (Jindrová & Labudová, 2020;Shields & Shooshtari, 2001) and even social capital (Carpiano, 2007;Dahl & Malmberg-Heimonen, 2010). In this theoretical context, empirical pre-pandemic studies showed how perceived (and therefore, also actual) health is socially conditioned.…”
Section: A Brief Review Of the Impact Of Covid-19 On Perceived Healthmentioning
confidence: 99%
“…The interest in perceived health lies in the capacity of this indicator to synthesize the objective circumstances of health (Shields & Shooshtari, 2001;Jindrová & Labudová, 2020). This helps to not only determine subjective perceptions, but also obtain a holistic view of an individual's situation in broader terms.…”
Section: Introductionmentioning
confidence: 99%